SEPARATION AND RETENTION BEHAVIOUR OF BENZIMIDAZOLE DERIVATIVES IN THIN LAYER CHROMATOGRAPHY ON SILICA GEL - Marijana Ačanski; Đura Vujić; Jovana Brkljača (Journal of Engineering & Processing Management, 2013)
The separation ability and retention behaviour of normal phase TLC on silica with eight nonaqueous eluents, has been studied by measuring the retention constants of a series of synthesized benzimidazoles. The separation ability and retention behaviour are discussed in terms of the nature of the solute and eluent.
Keywords: benzimidazoles; silica gel; non-aqueous eluents; retention